SARS-CoV-2 RBD-specific and NP-specific antibody response of healthcare workers in the westernmost Austrian state Vorarlberg: a prospective cohort study. Issue 5 (24th May 2022) - Atzl, Michele; Muendlein, Axel; Winder, Thomas; Fraunberger, Peter; Brandtner, Eva-Maria; Geiger, Kathrin; Klausberger, Miriam; Duerkop, Mark; Sprenger, Lukas; Mutschlechner, Beatrix; Volgger, Andreas; Benda, Magdalena; et al.
Abstract : Objectives: Austria, and particularly its westernmost federal state Vorarlberg, developed an extremely high incidence rate during the COVID-19 pandemic. Healthcare workers (HCWs) worldwide are known to have an increased risk of contracting the disease within the working environment and, therefore, the seroprevalence in this population is of particular interest. We thus aimed to analyse SARS-CoV-2-specific antibody dynamics in Vorarlberg HCWs. Design: Prospective cohort study of HCWs including testing at three different time points for the prevalence of anti-SARS-CoV-2 IgG antibodies specific for nucleocapsid protein (NP) and receptor-binding domain (RBD). Setting: All five state hospitals of Vorarlberg. Participants: A total of 395 HCWs, enrolled in June 2020 (time point 1 (t1 )), 2 months after the end of the first wave, retested between October and November at the beginning of the second wave (time point 2 (t2 )) and again at the downturn of the second wave in January 2021 (time point 3 (t3 )). Main outcomes: We assessed weak and strong seropositivity and associated factors, including demographic and clinical characteristics, symptoms consistent with COVID-19 infection, infections verified by reverse transcription PCR (RT-PCR) and vaccinations. Results: At t1, 3% of HCWs showed strong IgG-specific responses to either NP or RBD. At t2, the rate had increased to 4%, and at t3 to 14%. A strong response was found to be stable for up to 10 months. Overall, only 55% of seropositive specimen had antibodies against both antigens RBD and NP; 29% had only RBD-specific and 16% only NP-specific antibodies. Compared with the number of infections found by RT-PCR, the number of HCWs being seropositive was 38% higher. Conclusion and relevance: Serological testing based on only one antigen implicates the risk of missing infections; thus, the set of antigens should be broadened in the future. The seroprevalence among participating HCWs was comparable to the general population in Austria. Nevertheless, in view of undetected infections, monitoring and surveillance should be reconsidered.